Alcohol Hangover Increases Conflict Load via Faster Processing of Subliminal Information - Zink, Nicolas; Bensmann, Wiebke; Beste, Christian; Stock, Ann-Kathrin (Frontiers in Human Neuroscience, 2018)
The detrimental effects of acute alcohol intoxication and long-term alcohol (ab)use on cognition are well-known. Yet, only little is known about the cognitive effects of an acute alcohol hangover, even though it might affect executive functions associated with workplace performance or driving skills. Given that alcohol hangover may increase the speed of information accumulation, we assessed the behavioral effects of conflict load (induced by a subliminal prime) on cognitive control, as assessed via the Flanker effect. We employed a counter-balanced within-subject design, where n=25 healthy young males were tested once after a sober night and once after a night of experimentally induced heavy drinking of cheap brandy/red wine (2.6375 gr alcohol per estimated liter of body water within 2 – 3 hours). Alcohol hangover neither increased the cognitive conflicts induced by consciously processed distractors alone (i.e. the Flanker effect), nor modulated conflict adaptation (i.e. the Gratton effect). Instead, hangover potentiated the detrimental effects of conflicting subliminal primes on top-down cognitive conflicts. This effect was likely due to an increase in the speed of information accumulation from visual stimuli and the resulting increase in subliminal conflict load induced by incompatible primes. We further found the size of this effect to be positively correlated with age and subjective sleepiness during the hangover state, but the hangover effect remained significant even after correcting for those covariates. We further found no correlation of the behavioral effect with the subjective overall rating of hangover symptoms or the maximal alcohol breath alcohol concentration reached during prior intoxication. Taken together, our findings suggest that alcohol hangover may affect cognitive performance due to an increase in non-conscious processing of visual distractors. While the size of this effect might increase with age and sleepiness, it is not entirely dependent on those covariates and not necessarily related to subjective ratings of general hangover symptoms / impairment.